Semiosis and Ritual in the Act of Graduation of the Interpreter-Pianis - Rodríguez Uranga , Vivian; Vílchez Faria, Jacqueline (situArte, 2021)
This article presents an approach to the semiotic and anthropological analysis of the pianist performer's graduation ritual in society of Maracaibo, specifically in the “José Luís Paz” Music Conservatory. This object will be analyzed in the light of the contributions of the theory on the semiosis (González de Ávila, 2002) of culture (Lotman, 2000) and ritual analysis (Van Gennep, 1999; Turner, 1988, 1999; Douglas, 1973) in its interrelationship with the myths and musical beliefs of Western culture. Based on interviews, ethnographic observation and semiotic analysis (Finol, 2006), we seek to describe the characteristics of ritual and the historical construction of meaning, simultaneously considering the social signs and the society that produces them.